-4u-3=9(u+4)

Simple and best practice solution for -4u-3=9(u+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4u-3=9(u+4) equation:


Simplifying
-4u + -3 = 9(u + 4)

Reorder the terms:
-3 + -4u = 9(u + 4)

Reorder the terms:
-3 + -4u = 9(4 + u)
-3 + -4u = (4 * 9 + u * 9)
-3 + -4u = (36 + 9u)

Solving
-3 + -4u = 36 + 9u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-9u' to each side of the equation.
-3 + -4u + -9u = 36 + 9u + -9u

Combine like terms: -4u + -9u = -13u
-3 + -13u = 36 + 9u + -9u

Combine like terms: 9u + -9u = 0
-3 + -13u = 36 + 0
-3 + -13u = 36

Add '3' to each side of the equation.
-3 + 3 + -13u = 36 + 3

Combine like terms: -3 + 3 = 0
0 + -13u = 36 + 3
-13u = 36 + 3

Combine like terms: 36 + 3 = 39
-13u = 39

Divide each side by '-13'.
u = -3

Simplifying
u = -3

See similar equations:

| -8(4+n)-8= | | 11x=222 | | 0.22y+0.03(y+4000)=2370 | | 3c+9c= | | q-9=-19 | | 4v-15=49 | | -9(v-4)=5v+4 | | .4x-73=90 | | -8(4+n)= | | 9-9=-19 | | 5+-(11)-(-11)= | | 15u+5v-3u+17v= | | -19+p=-9 | | 7(2x-10)-3=7(x-5)+4 | | -19+p=9 | | 8=16.9-a | | cosine(x)=-0.25 | | 8x-4(1+X)= | | 10=.11(0)+b | | X*x+1=101 | | 6/5÷6/ | | 2x+3+x=128 | | F(x)=log(x+7)+4 | | 6/5÷6/8 | | 7x-6+10x-5= | | 3c+12=5c+11.44 | | 6(-7d+12d)= | | -6w+8=-2(w+8) | | -25+n=-37 | | g(x)=x-13 | | (-5)(3)(-3)= | | (X/2)-10=x/2 |

Equations solver categories